Reproductive risk factors associated with breast cancer in young women by molecular subtype. (December 2022) - Ruddy, Kathryn J.; Vierkant, Robert A.; Jahan, Nusrat; Higgins, Alexandra; Partridge, Ann; Larson, Nicole; Radisky, Derek C.; Couch, Fergus; Olson, Janet; Sherman, Mark E.
Abstract: Background: Few studies have examined detailed features of pregnancy and the postpartum period as potential risk factors for early onset breast cancer (BC) by molecular subtype. These data may have value for improving risk assessment and prevention. Methods: We surveyed parous enrollees in the prospective Mayo Clinic Breast Disease Registry (MCBDR) who had been diagnosed with BC at age <55 years between 2015 and 2020. Summary statistics were used to describe survey responses and reproductive risk factors by BC subtype (defined by estrogen/progesterone receptors and human epidermal growth factor receptor expression, nurse-abstracted from the medical record). Associations were assessed with Kruskal-Wallis and Chi-Square tests, followed by age-adjusted linear and logistic regression models. We compared results from this parous cohort to those from a separate cohort of nulliparous MCBDR participants with BC diagnosed at age <55 years. Results: In 436 parous respondents with subtype data abstracted, we identified a higher frequency of BRCA1 mutation, earlier age at diagnosis, and lower BI in patients with triple negative BC. Comparing parous to nulliparous young women with breast cancer, the proportion with TNBC was larger in the latter (12.2% vs. 15.1%, p = 0.03). Conclusions: Early age at diagnosis and deleterious BRCA1 mutation were more frequent among TNBC patients. In addition, parous young women with TNBC had a lower BI than those with other BC subtypes, a hypothesis-generating finding that supports the need for additional research on the cycle of pregnancy-lactation-postpartum involution and BC etiology. Highlights: We surveyed survivors of young-onset breast cancer to study subtype-specific associations with pregnancies and lactation. Triple negative tumors were associated with more BRCA1 mutations and younger age at diagnosis than other tumor subtypes. In parous women, lower birth indices (summed times between births and cancer onset) were found with triple negative tumors.